2019
DOI: 10.2135/cropsci2018.09.0589
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Cover Crop Management on Level of Weed Suppression: A Meta‐Analysis

Abstract: We conducted a previous systematic and meta‐analysis review that showed differences in results from studies that evaluated the effectiveness of cover crops for weed suppression in cropping systems; these differences were largely due to management approaches used in growing the cover crop and main crop. The current meta‐analysis provides a quantitative review on how cover crop and main crop management practices influence the impact of cover crops on weed suppression. The meta‐analysis used observations from 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 53 publications
(129 reference statements)
8
102
0
10
Order By: Relevance
“…Generation of dynamic spatial and temporal diverse agroecological conditions are possible through the implementation of management practices, such as the use of grazed and ungrazed pasture phases [86], cover crops [87], choice of competitive cultivars [88], changes in cultural practices such as seeding and harvest time, crop row spacing, density and orientation [89], implementation of soil tillage [83], and management of fence lines and field margins [90], just to mention a few. These diverse agroecological conditions imply environmental changes in fluctuating temperatures and light intensity and quality (red/far red ratio) at soil levels and under crop canopies and demand of plant resources together, which in turn may bring changes in soil chemical and physical properties.…”
Section: Implications Of Fitness Costs To Resistance Managementmentioning
confidence: 99%
“…Generation of dynamic spatial and temporal diverse agroecological conditions are possible through the implementation of management practices, such as the use of grazed and ungrazed pasture phases [86], cover crops [87], choice of competitive cultivars [88], changes in cultural practices such as seeding and harvest time, crop row spacing, density and orientation [89], implementation of soil tillage [83], and management of fence lines and field margins [90], just to mention a few. These diverse agroecological conditions imply environmental changes in fluctuating temperatures and light intensity and quality (red/far red ratio) at soil levels and under crop canopies and demand of plant resources together, which in turn may bring changes in soil chemical and physical properties.…”
Section: Implications Of Fitness Costs To Resistance Managementmentioning
confidence: 99%
“…In NT dryland systems, CC biomass production varies greatly because of variable precipitation amount, crop rotation, CC species, planting time, seeding rate, and soil type. In a recent meta-analysis, Osipitan et al (2019) showed that CC management decisions, including selection of CC species, planting season, planting date, seeding rate, termination date, delay in main crop planting after termination of CCs, and tillage system, all can influence the effective use of CCs for weed suppression. Here, we briefly review major agronomic practices and challenges in growing CCs for weed suppression in NT semiarid regions of the U.S. Great Plains.…”
Section: Agronomic Considerations For Integrating Cover Crops In No-tmentioning
confidence: 99%
“…Therefore, some agronomical practices, such as agro-ecological service crops and soil tillage, that generally have a great impact on weed establishment and growth [5,6] must be evaluated in relation to quinoa cultivation. In fact, the combination of agro-ecological service crops and the arrangement of their residues could determine different levels of weed responses based on the qualitative and quantitative characteristics of the agro-ecological service crop residues and the type of soil tillage adopted [7]. The information obtained from such studies could support farmers in the decision process focused on a suitable approach to manage weeds in quinoa crops.…”
Section: Introductionmentioning
confidence: 99%